Ecomorphological Traits of Bird Communities Along Urbanization Gradient in A Tropical Peri-Urban Landscape of Bogor, Indonesia - Septian Putra Adi Nugroho; Ani Mardiastuti; Yeni Aryati Mulyani; Dede Aulia Rahman; Anik Budhi Dharmayanthi; Yohanna (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
In Indonesia, peri-urban landscapes are rapidly developing and characterized by mosaics of natural, agricultural, and developed areas. This study investigated the effects of environmental differences across an urbanization gradient on bird community structure and the composition of ecomorphological traits within the tropical peri-urban landscape of Bogor, Indonesia. Field surveys were carried out between September and February from 2020 to 2023 in five habitats: secondary forest, plantation, riparian, built-up area, and farmland. Habitat conditions were characterized using Leaf Area Index (LAI), Normalized Difference Vegetation Index (NDVI), land-cover composition, and vegetation measurements. Bird communities were evaluated through standardized point-countsurveys and the calculation of diversity indices. Relationships between habitat variables and bird ecomorphological traits were assessed using Generalized Linear Mixed Models (GLMMs) and modelbased fourth-corner analysis. In total, 19,637 individuals representing 77 species and 35 families were recorded. Species richness was greatest in secondary forest and lowest in farmland, while the Shannon–Wiener index declined from 3.136 to 2.218 along the gradient from less disturbed to more modified habitats. Tree species richness emerged as a key predictor of several ecomorphological traits. Structurally complex habitats favored arboreal, frugivorous, nectarivorous, and cavity-nesting birds, whereas farmland and built-up areas were dominated by generalist, aerial, and omnivorous species. These patterns indicate that vegetation simplification may drive ecological filtering and functional homogenization. Therefore, in tropical urban environments with rapid urbanization, conservation should emphasize the preservation of remnant trees, enhancement of multilayered vegetation, and restoration of riparian corridors to boost habitat variability and connectivity for bird conservation.